1989
DOI: 10.1002/1097-0142(19890201)63:3<539::aid-cncr2820630323>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

An index for estimating the probability of lymph node metastasis in rectal cancers. Lymph node metastasis and the histopathology of actively invasive regions of cancer

Abstract: We examined resected specimens from 40 cases of advanced rectal cancer to determine the extent of microtubular cancer nests and undifferentiated cancer cells (budding). We investigated the relationship between this budding and lymphatic invasion (ly), venous invasion (v), and lymph node metastasis (n), respectively. Moreover, we examined the relationship between ly, budding, and n in the preoperative biopsy specimens of 112 patients, including those of the 40 cases mentioned above. The degree of budding, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
198
2
9

Year Published

2001
2001
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 222 publications
(217 citation statements)
references
References 8 publications
8
198
2
9
Order By: Relevance
“…There is a strong association between budding and the presence of lymph node metastases and lymphovascular invasion, 11,12,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] defined by the presence of tumor cells within an endothelium-lined space, and it has been suggested that buds represent the part of the tumor that has gained the ability to invade lymphatics and vascular channels. This idea is supported by two intriguing morphological studies: Morodomi et al 33 examined serial sections of high-budding areas to demonstrate that budding nests are often found adjacent to areas of lymphovascular space invasion, and, in a more recent study, Ohtsuki et al 31 performed double staining for anti-cytokeratin antibodies and anti-lymphatic antibodies, finding that a number of 'buds' at the invasive edge of a tumor are in fact located in small lymphatic spaces.…”
Section: Morphological Featuresmentioning
confidence: 99%
See 4 more Smart Citations
“…There is a strong association between budding and the presence of lymph node metastases and lymphovascular invasion, 11,12,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] defined by the presence of tumor cells within an endothelium-lined space, and it has been suggested that buds represent the part of the tumor that has gained the ability to invade lymphatics and vascular channels. This idea is supported by two intriguing morphological studies: Morodomi et al 33 examined serial sections of high-budding areas to demonstrate that budding nests are often found adjacent to areas of lymphovascular space invasion, and, in a more recent study, Ohtsuki et al 31 performed double staining for anti-cytokeratin antibodies and anti-lymphatic antibodies, finding that a number of 'buds' at the invasive edge of a tumor are in fact located in small lymphatic spaces.…”
Section: Morphological Featuresmentioning
confidence: 99%
“…A few tumor-budding studies have used vascular markers and/or elastic stains to assess vascular invasion, 11,12,19,22,26,32,37,38 but only four have analyzed the relationship between budding and vascular invasion: Kazama et al 22 found no relationship between budding and vascular invasion, whereas three other studies have reported a statistically significant correlation between budding and venous invasion, though the association was not as pronounced as the relationship with lymphatic invasion and lymph node metastases. 11,12,32 The tumor-host interaction at the invasive front may be of prognostic importance in the setting of tumor budding. Several studies have shown peritumoral lymphocytic infiltration to be an independent prognostic factor in colorectal carcinoma.…”
Section: Morphological Featuresmentioning
confidence: 99%
See 3 more Smart Citations